Epidemiology of binocular vision anomalies in children: a narrative review (African Scientific Reports, 2026)
The ability to see simultaneously with both eyes working together is known as binocular single vision. A healthy anatomical, motor, and sensory system is necessary for single binocular vision. Thus, binocular vision anomalies are caused by abnormalities in the operation of all three systems that interfere with single binocular vision. This study's objective is to examine the frequency and risk factors of binocular vision abnormalities in children in secondary school, ages 10 to 18. The study adopted a non-systematic review methodology. Using search engines like PubMed and Google Scholar, as well as the Mendeley reference library for citation, published material from Nigeria, sub-Saharan Africa, and throughout the world was found and evaluated. The results indicate that between 34.3% and 76.5% of people have binocular vision abnormalities. Both strabismic (SBVA) and non-strabismic binocular vision abnormalities (NSBVA) were risk factors for BVAs, with respective prevalence of 12.85% for SBVA and 76.5% for NSBVA. In conclusion, screening and management techniques that focus on these visual disorders are required to avoid interference with educational and social advancement, considering the significance of visual abilities in learning and academic accomplishments. This review therefore, emphasizes the necessity of conducting a comprehensive evaluation of binocular vision status of children as prerequisite for admittance of students into schools.
Keywords: Accommodation anomalies; Amblyopia; Binocular vision anomalies; Convergence insufficiency; Strabismus